Tree species diversity adapted to Pinus merkusii forests in Gunung Ciremai National Park, West Java, Indonesia - TOTO SUPARTONO; ILHAM ADHYA; DEDE KOSASIH; WILLY WILDANI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Supartono T, Adhya I, Kosasih D, Wildani W. 2023. Tree species diversity adapted to Pinus merkusii forests in Gunung Ciremai National Park, West Java, Indonesia. Biodiversitas 24: 4314-4323. One of the challenges faced in rehabilitating pine forests in conservation areas is the limited information on plant species capable of adapting to these ecosystems. This study aimed to analyze the diversity of tree species that grow and adapt to pine forests and the relationship of natural forests with the vegetation characteristics of pine forests. The research was conducted in pine forests bordering natural forests and far from natural forests using the sample plot method. The study recorded 44 species from 27 families of seedlings, 46 species from 21 families of saplings, 25 species from 18 families of poles, and 24 species from 17 families of trees. Accumulation of species from all growth stages recorded 83 species (76 local species and 7 cultivated species) from 39 families. Based on the species accumulation curve, pine forests adjacent to natural forests have more species than those far from natural forests. Individual and family density in pine forests adjacent to natural forests were also higher than the density of these two variables in pine forests far from natural forests. Furthermore, both the pine forest adjacent to the natural forest and that far from the natural forest, each has its own species peculiarities. The results indicate that the existence of natural forests has an important role as a source of biodiversity for the surrounding ecosystem. As an implication of this study, species that can grow to the level of poles and trees can be recommended as rehabilitation plants in the Pinus merkusii Jungh. & de Vriese forests in Gunung Ciremai National Park, Indonesia because pine is not a local species and the allelopathy it releases can reduce plant diversity.